20, 000 years of Nile River dynamics and environmental changes in the Nile catchment area as inferred from Nile upper continental slope sediments. (15th December 2015) - Revel, Marie; Ducassou, E.; Skonieczny, C.; Colin, C.; Bastian, L.; Bosch, D.; Migeon, S.; Mascle, J.
Abstract: Multi-proxy analysis of two marine sediment cores (MS27PT and MD04-2726) from the Nile continental slope provides evidence of changes in Nile sediment discharge related to changes in Ethiopian African Monsoon (EAM) precipitation, and allows us to reconstruct changes in Nile River runoff, vegetation and erosion in the Nile headwaters. Sediment element composition and neodymium isotopic composition reveal significant changes in clastic sediment provenance, with sources oscillating between a Saharan aeolian contribution during the Last Glacial Maximum/deglacial transition and during the Late Holocene, and a Blue/Atbara Nile fluvial contribution during the African Humid Period (AHP). This study provides a new understanding of past environmental changes. Between 14.6 and 14.13 ka there was a major input of sediments from the Ethiopian Highlands, consistent with a stronger EAM at that time. Climate in the Nile basin was wetter between 14.8 and 8.4 ka, with a corresponding increase in Blue Nile water and sediment discharge via the main Nile into the Eastern Mediterranean. The gradual climatic transition from the AHP to the present-day dry climate was reflected in a decrease in Blue Nile sediment deposition and flood discharge between 8.4 and 3.7 ka, with aridity at a maximum between 3.7 and 2.6 ka. The onset of drier conditions in the Blue Nile basin seems to have begun before the 8.2 ka cooling event in the North Atlantic. We speculate that the climatic change from the wet AHP to the dry late Holocene may have been a result of a break in the low latitude dynamic equilibrium between climate, vegetation and erosion, which may in turn have affected the climate in higher latitudes. Reduced Nile flow may also have had an impact on Levantine Intermediate Water originating in the Eastern Mediterranean through an increase in intermediate water formation. Highlights: Invigoration of the Ethiopian African Monsoon at ∼14, 800 Years. Maxima of the summer Ethiopian Monsoon precipitation coincide with the maximum North Hemisphere summer insolation. Onset of drier conditions in the Blue Nile basin dated at ~8.4 ka appears to have preceded the North Atlantic 8.2 event. Hydrologic changes in the tropics may be important drivers of climate at higher latitudes during the Holocene.